Hierarchical and coaxial yarn with combined conductance stability and sensing capability for wearable electronics. (December 2022) - Dou, Lu; Zheng, Xiaohao; Yuan, Man; Li, Daiqi; Zhao, Zhong; Tang, Wenyang; Fu, Chiyu; Xia, Zhigang; Cai, Guangming
Highlights: Strain sensitive and resistance stable composite yarn was fabricated with a novel hierarchical and coaxial structure. Strain-insensitive conductance layer remained high conductivity under different conditions, while coaxial sensing layer showed remarkable sensing property. Multilayer composite yarn showed a stable and stretchable electric heating performance. Potential applications include human motion monitoring and flexible multipoint touch arrays were demonstrated. Abstract: Yarn-based sensors are essential units for smart textiles and wearable devices. Most reported fiber sensors, however, are sensitive or stable in conductivity under stretching, limiting their applicability. Herein, we report a strategy for fabricating a specific sensor based on liquid metal/tube/CNT polyester yarn (LTCPY) via friction spinning. The inside of the multilayer composite yarn served as a wire with a broad strain range (0%–300%) and ultrahigh conductivity (3.78 × 10 5 S/m). The conductivity of the yarn remains at a relatively high level when it is stretched to 250% strain. The external structure endows the sensor with good sensing performance (GF of 6.73 under an elongation of 175%-203%) and recoverability (1000 cycles). The combination of conductance stability and good sensing properties contributes to the application potential of LTCPY as portable conductive wires, stretchable heaters, and wearable sensors to monitor human activities. Moreover, LTCPY can be easily woven into fabrics, introducing a new strategy for the mass production of electronic textiles. Graphical abstract: Image, graphical abstract